Pengembangan LKPD Berbasis Liveworksheets Pada Materi Sel Kelas XI Mahidayatul Insan Palangka Raya - Savitri, Shanty; Haryono, Agus; Rahmi, Ennike Gusti; Fahrina, Ririn; Araina, Elga; Uda, Saritha Kittie; Yusiana, Arlinda Amelia; Windasari, Asi (UIR Press, 2024)
The learning carried out in class XI MA Hidayatul Insan uses LKPD which is still limited and has not supported the learning needs of students, so that the learning that takes place is not optimal, the learning process is less interactive, inspiring, and less motivating students to actively participate. Teachers have not maximized the use of LKPD that is attractive to students. This study aims to determine the structure, feasibility, and student response to LKPD based on Liveworksheet Cell material. This research was conducted in class XI MA Hidayatul Insan Palangka Raya and will use data collection instruments in the form of interview guidelines and to determine the quality of E-LKPD using validation from materials, media experts, and linguists. Based on what has been described, it is necessary to conduct research with the title